Complete sequence of the Rous sarcoma virus env gene: identification of structural and functional regions of its product. - Hunter, E (1983)
The amino-terminal amino acid sequences of gp85 and gp37, the envelope glycoproteins of Rous sarcoma virus (RSV), were determined. Alignment of these sequences with the amino acid sequence predicted from the complete nucleotide sequence of the Prague strain of RSV, subgroup C (PR-C), has allowed us to delineate the env gene-coding region of this virus. The coding sequences for gp85 and gp37 have been placed in an open reading frame that extends from nucleotide 5045 to nucleotide 6862 and predict sizes of 341 amino acids (36,962 molecular weight) for gp85 and 198 amino acids (21,566 molecular weight) for gp37. Carbohydrate makes a significant contribution to the observed molecular weights of these polypeptides--the amino acid sequence contains 14 potential glycosylation sites (Asn-X-Ser/Thr) in gp85 and two in gp37. Experiments aimed at estimating the number of carbohydrate side chains yielded results consistent with most or all of these sites being occupied. Although an initiation codon is located early (codon 4) in the open reading frame, it is likely that splicing yields an mRNA on which translation initiates at the same AUG as that of the gag gene to produce a nascent polypeptide in which gp85 is preceded by a 62-amino-acid-long leader peptide. This leader contains the hydrophobic sequence (signal sequence) necessary for translocation across the endoplasmic reticulum and is completely removed from the env gene product during translation. The polyprotein precursor, Pr95env, is cleaved to gp85 and gp37 at the carboxyl side of the basic sequence:-Arg-Arg-Lys-Arg-. gp85 is attached through a disulphide linkage to gp37, and although the positions of the cysteines involved in this linkage are not known, the presence of a 27-amino-acid-long hydrophobic region at the carboxy-terminus of gp37 is consistent with its role as a membrane anchor for the viral glycoprotein complex. The location of host range variable regions with respect to the possible tertiary structure of the complex is discussed.